CO2 concentration in day care centres is related to weezing in attending children - Carreiro-Martins, Pedro (2015)
Poor ventilation at day care centres (DCCs) was already reported, although its effects on attending children are not clear. This study aimed to evaluate the association between wheezing in children and indoor CO2 (a ventilation surrogate marker) in DCC and to identify behaviours and building characteristics potentially related to CO2. In phase I, 45 DCCs from Lisbon and Oporto (Portugal) were selected through a proportional stratified random sampling. In phase II, 3 months later, 19 DCCs were further reassessed after cluster analysis for the greatest difference comparison. In both phases, children’s respiratory health was assessed by ISAAC-derived questionnaires. Indoor CO2 concentrations and buildingcharacteristics of the DCC were evaluated in both phases, using complementary methods. Mixed effect models were used to analyze the data. In phase I, which included 3,186 children (mean age 3.1±1.5 years), indoor CO2 concentration in the DCC rooms was associated with reported wheezing in the past 12months (27.5 %) (adjusted odds ratio (OR) for each increase of 200 ppm 1.04, 95 % CI 1:01 to 1:07). In phase II, the association in the subsample of 1,196 children seen in 19 out of the initial 45 DCCs was not significant (adjusted OR 1.02, 95 % CI 0.96 to 1.08). Indoor CO2 concentration was inversely associated with the practices of opening windows and internal doors and with higher wind velocity. A positive trend was observed between CO2 and prevalence of reported asthma (4.7 %). Conclusion: Improved ventilation is needed to achieve a healthier indoor environment in DCC.